Asymmetric Total Synthesis of (+)-Minfiensine by an Asymmetric Cascade Cyclization Strategy - Zhang, Ze-Xin; Chen, Si-Cong; Jiao, Lei (Synlett, 2017)
The Strychnos alkaloid minfiensine and a series of akuammiline alkaloids, such as vincorine, aspidophylline A, and picrinine, possess a common core skeleton, a 4a,9a-heterocycle-fused tetrahydrocarbazole. Efficient construction of this core structure in a highly enantioselective manner would facilitate the total synthesis of these alkaloids. In this article, we briefly summarize the established strategies for obtaining this core structure, together with the corresponding total-synthesis routes, and we describe our own effort on the development of a new strategy, the asymmetric cascade dearomative cyclization, for the efficient total synthesis of (+)-minfiensine.
Keywords: alkaloids; indoles; minfiensine; asymmetric cascade cyclization; asymmetric allylic alkylation; palladium catalysis